Transformation of metallothionein gene (eiMT1) from eleusine indica into tobacco, nicotiana tabacum by Agrobacterium tumefaciens - Nik Marzuki Sidik,; Roslina Mat Yazid,; Che Radziah Che Mohd. Zain,; Ismanizan Ismail, (Universiti Kebangsaan Malaysia, 2010)
Metallothioneins (MTs) are low molecular weight, cysteine-rich metal-binding proteins found in a wide range of organisms including bacteria, fungi, plant and animal. Plant MTs are thought to play a role in metal metabolism and detoxification via chelating of the metal ions. This unique feature results in the interest to isolate gene from goosegrass, Eleusine indica. eiMT1 cDNA was cloned into pBI121 binary vector for the transformation into tobacco by Agrobacterium tumefaciens. Screening of transgenic plants was conducted using three specially designed primers, CMTF and CMTR and 35SF and PMTR, and a pair of gene specific primers, MTFS2 and MTRS2. The primer pairs used successfully produced expected DNA fragments of 270 bp, 1.1 kb and 170 bp, respectively. Sequencing and sequence analysis of the 170 bp fragment was 100 % identical to the eiMT1. Gene expression study via reverse transcription-polymerase chain reaction approach showed that the transgene was successfully expressed in 11 of the 19 transgenic plants.